Developing English-Based Pop Up Book Media to Increase the Early Childhood’s Motivation - Suhono; Wiwied Pratiwi; Bambang Ariyanto; Andi Lala (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2022)
This study aims to develop a Pop Up Book media for increasing motivations early childhood. Therefore, learning media is needed that can facilitate students in learning, one of which is Pop Up Book media. Pop-up book media. Pop-up books are books that have moving parts or have three-dimensional elements and provide a more interesting visualization of the story, starting from the display of images that can move when the page is opened. With the guidance of the teacher, students can write descriptive text by looking at the pictures and vocabulary in the Pop Up Book. The design of this research is research and development or research (R&D).The development model used is ADDIE (analysis, design, development, evaluation, implementation) using the Dick and carry development model. The results of this study indicate that the level of product feasibility by material experts and media experts is included in the valid category and is suitable for use but needs to be revised. From the results of the design expert data, the results of the Pop-Up Book learning media are valid and feasible to be applied learning to increase early childhood’s motivations. Based on the results of the validation that has been carried out by the material expert, it can be seen that validation of the material expert obtained an average score of 96,66% With the criteria “very good”. And based on the validation results that have been carried out by design experts, it can be seen that the value is 96% with criteria “very good”.